2006
DOI: 10.1007/s00041-006-6022-0
|View full text |Cite
|
Sign up to set email alerts
|

Density, Overcompleteness, and Localization of Frames. I. Theory

Abstract: ABSTRACT. Frames have applications in numerous fields of mathematics and engineering. The fundamental property of frames which makes them so useful is their overcompleteness. In most applications, it is this overcompleteness that is exploited to yield a decomposition that is more stable, more robust, or more compact than is possible using nonredundant systems. This work presents a quantitative framework for describing the overcompleteness of frames. It introduces notions of localization and approximation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
231
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 136 publications
(242 citation statements)
references
References 55 publications
(69 reference statements)
3
231
0
1
Order By: Relevance
“…In the special case where the generator f is a Gaussian function, it has been shown (See [22,24,25] and Gröchenig's book [16]) that the lower density of the set Λ is greater than one if and only if F is a frame for the whole space L 2 (R). This result, combined with results from [1,2], shows that property 4) holds for Gaussian generators. To see this, assume that g is Gaussian, Λ ⊂ R 2 and (g, Λ) generates a Gabor frame for L 2 (R).…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…In the special case where the generator f is a Gaussian function, it has been shown (See [22,24,25] and Gröchenig's book [16]) that the lower density of the set Λ is greater than one if and only if F is a frame for the whole space L 2 (R). This result, combined with results from [1,2], shows that property 4) holds for Gaussian generators. To see this, assume that g is Gaussian, Λ ⊂ R 2 and (g, Λ) generates a Gabor frame for L 2 (R).…”
Section: Introductionsupporting
confidence: 66%
“…In [3], a redundancy function for infinite frames was defined. It was shown that this redundancy function, when translated to the localized setting dealt with in [1], corresponded to the density measures described in [3]. Both papers identify this density function as a good candidate for redundancy, show that the function satisfies properties 1)-3) above and remark that a proper notion of redundancy should also possess property 4).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations